Risk factors for bone cement displacement after percutaneous vertebral augmentation for osteoporotic vertebral compression fractures - Gao, Xiangcheng; Du, Jinpeng; Gao, Lin; Hao, Dingjun; Hui, Hua; He, Baorong; Yan, Liang (Frontiers in Surgery, 2022)
Purpose To explore the risk factors of bone cement displacement after percutaneous vertebral augmentation (PVA) in patients with osteoporotic vertebral compression fracture (OVCF). Methods We retrospectively reviewed the records of 1538 patients with OVCF treated with percutaneous vertebroplasty (PVP) or percutaneous vertebroplasty (PKP) from January 2016 to June 2021. Patients were divided into bone cement displacement group (n=78) and bone cement non-displacement group (n=1 460) according to the radiographic images. Possible risk factors for bone cement displacement were noted, including age, gender, body mass index (BMI), bone mineral density (BMD), underlying disease, number of fractured vertebrae, involved vertebral segment, surgical method, surgical approach, vertebral height, Cobb angle, cement leakage, the viscosity of bone cement, bone cement diffuse ratio, degree of bone cement interweaving, sagittal bone cement placement, targeted location of bone cement, the distance between the bone cement and the upper and lower endplates, the time of wearing brace and postoperative osteoporosis treatment. Risk factors were identified with univariate and multivariate logistic regressions and the discrimination ability of the predictive indicators was evaluated using area under the curve (AUC) of the receiver operating characteristic (ROC). Results In multivariate regression, independent risk factors for bone cement displacement included: high restoration of Cobb angle (OR=2.019, 95%[CI] 1.545-4.852, P<0.001), cement leakage (anterior edge) (OR=1.727, 95%[CI] 1.05-2.20, P<0.001), small degree of bone cement interweaving (OR=1.917, 95%[CI] 1.129-2.747, P<0.001), non-targeted location of bone cement(OR=2.323, 95%[CI] 1.645-4.134, P<0.001), short duration of brace wearing (OR=3.207, 95%[CI] 2.036-4.348, P<0.001) and postoperative osteoporosis treatment (OR=0.422, 95% CI=0.323–0.547, P<0.001). The AUCs for the high restoration of Cobb angle, cement leakage (anterior edge), small degree of bone cement interweaving, non-targeted location of bone cement, short duration of brace wearing and non-postoperative osteoporosis treatment were 0.784 (95% CI, 0.747–0.821), 0.811 (95% CI 0.764–0.859), 0.917 (95%CI 0.864-0.970), 0.610 (95%CI 0.552-0.669), 0.854 (95%CI 0.816-0.892) and 0.756 (95% CI, 0.712–0.800), respectively. Conclusion High restoration of Cobb angle, cement leakage (anterior edge), small degree of bone cement interweaving, non-targeted location of bone cement, short duration of brace wearing and non-postoperative osteoporosis treatment were the independent risk factors of bone cement displacement after PVA.